P76-F DYNC1H1 gene mutation in an Estonian family. Issue 7 (July 2019) - Lunge, Kaidi; Sander, Valentin; Talvik, Inga; Reimand, Tiia
Abstract : Background: DYNC1H1 gene mutations have been related to many neuromuscular diseases, including autosomal dominant Charcot-Marie-Tooth disease type 2O and autosomal dominant spinal muscular atrophy, with lower extremity predominance (SMA-LED). SMA-LED is a disease with large clinical variability. The early clinical signs are feet deformities, delayed walking and muscle weakness. Material and methods: We will present the case report with EMG findings of the family with SMA-LED confirmed by genetic analysis. Results: The diagnosis was confirmed with TrueSight One panel covering 4813 genes. Mutation M_001376.4(DYNC1H1):c.1869C > G p.Phe623Leu in DYNC1H1 gene was detected in mother and in two younger children of the family. Conclusion: When EMG examination shows neurogenic changes and signs of spinal atrophy, but SMN1 gene test is negative, then it is important to think about rare forms of spinal muscular atrophies.